RECONSTRUCTING A MODEL OF LEGAL PROTECTION FOR CORONAVIRUS DISEASE 19 PANDEMIC IN INDONESIA - Mukhtar Lutfi; Muhammad Mutawalli; Muhammad Saleh Tajuddin; Andi Tenri Yeyeng (Universitas Syiah Kuala, 2023)
This article examines the legal protection model due to the corona virus disease (Covid-19) in Indonesia. With the global impact of the Covid19 virus pandemic, the country's activities and survival have come to a halt. This article determines the form of Reconstruction of the Legal Protection Model for the Impact of the Global Corona Virus Disease 19 Pandemic in Indonesia. This study uses normative methods that are doctrinal, analytical, exploratory and explanatory with qualitative analysis. The results shows that the Indonesian state relies on largescale social funding policies (PSBB) with a disaster scheme that is recommended as a health emergency. It is an ideal model of legal protection against the impact of COVID-19 based on human rights (HAM) and the supremacy of law which are integrated and connected to resolve multisectoral impact problems. The multidimensional protection needs, including social, health, education, culture, religion, economics and finance, business trade and industry, labor, employment, transportation, environment, tourism, sports, security, politics and law is requited